2015
DOI: 10.1111/cfs.12225
|View full text |Cite
|
Sign up to set email alerts
|

Tackling the problem of teenage pregnancy in looked‐after children: a peer mentoring approach

Abstract: A B S T R AC TTeenage pregnancy is associated with adverse health and social outcomes, even after adjusting for prior disadvantage, and is recognized as a major public health issue. Rates of teenage pregnancy in the UK are among the highest in Europe. Interventions introduced in the past decade to address the problem, such as improved sex and relationships education in schools, have been accompanied by a fall in teenage pregnancy rates in the UK. However, this decline has not been mirrored among looked-after c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
(108 reference statements)
0
10
0
Order By: Relevance
“…Compared to other teenagers, young care leavers tend to have poor sexual and reproductive health (Combs et al., 2022), including poorer contraceptive use, increased rates of transmission of sexually transmitted infections (STIs) and HIV (Nixon, Elliott and Henderson, 2019). International evidence suggests that care leavers, including those in the UK, are also more likely to experience unintended early pregnancy/parenthood, are less likely to choose pregnancy termination, and more likely to experience the removal of children from their care (Buttram, Pagano and Kurtz, 2019; Chase et al., 2006; Combs et al., 2018b; Combs et al., 2022; Craine et al., 2014; Häggman-Laitila, Salokekkilä and Karki, 2018; Mezey et al., 2017; Purtell, Mendes and Saunders, 2020; Roberts et al., 2017; Vinnerljung, Franzén and Danielsson, 2007; Wall-Wieler et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to other teenagers, young care leavers tend to have poor sexual and reproductive health (Combs et al., 2022), including poorer contraceptive use, increased rates of transmission of sexually transmitted infections (STIs) and HIV (Nixon, Elliott and Henderson, 2019). International evidence suggests that care leavers, including those in the UK, are also more likely to experience unintended early pregnancy/parenthood, are less likely to choose pregnancy termination, and more likely to experience the removal of children from their care (Buttram, Pagano and Kurtz, 2019; Chase et al., 2006; Combs et al., 2018b; Combs et al., 2022; Craine et al., 2014; Häggman-Laitila, Salokekkilä and Karki, 2018; Mezey et al., 2017; Purtell, Mendes and Saunders, 2020; Roberts et al., 2017; Vinnerljung, Franzén and Danielsson, 2007; Wall-Wieler et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While few studies consider whether pregnancies were wanted and/or intended (Ethier, 2022), it is important to recognise that early parenthood may be considered as a positive experience for some, and for others it may be a less positive choice (Mezey et al., 2017; Roberts et al., 2017). For example, evidence from the US and the UK highlights that early motherhood may be perceived as a way of rectifying earlier adverse experiences, providing stability and meeting emotional needs, a chance to be part of a family, and motivation and opportunity for achievement and responsibility (Aparicio, Pecukonis and O’Neale, 2015; Chase et al., 2006; Knight, Chase and Aggleton, 2006; Mezey et al., 2017; Radey et al., 2016). However, one recent US study of looked after children suggested that only 10% held pro-pregnancy attitudes, with over half expressing anti-pregnancy attitudes, and the remaining one-third holding ambivalent beliefs (Combs et al., 2018a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In England, in 2019/20, there were 43,000 care leavers aged 17 to 21 (Foley et al, 2022). These young people are more likely than their peers to have experienced Adverse Childhood Experiences (Simkiss, 2019), to be involved with criminal justice services (Gooch et al, 2022), become a teenage parent (Mezey et al, 2017; Roberts, 2017), and experience psychological distress or mental health issues (Adley & Jupp Kina, 2017; Butterworth et al, 2017), housing problems and/or homelessness (Liabo et al, 2016; Wade & Dixon, 2006). They are also less likely to achieve academically in school, attend higher education (Evans et al, 2017; Hollingworth & Jackson, 2016; Mannay et al, 2017; O'Higgins et al, 2017), or enter into stable employment (Gypen et al, 2017) than their non‐looked after peers.…”
Section: Introductionmentioning
confidence: 99%
“…Many young people leaving care are likely to experience multiple and bewildering transitions that evoke feelings of instability, powerlessness, unpreparedness, abandonment and mistrust (Butterworth et al, 2017;Stein, 2012). Overall, relative to their peers, care leavers are more likely to have a conviction (Viner and Taylor, 2005;Schofield et al, 2014), become a young parent (Roberts, 2017;Mezey et al, 2017), experience social exclusion (Stein, 2006) and mental ill health (Viner and Taylor, 2005). They are less likely to achieve academically in school (O'Higgins et al, 2015;Mannay et al, 2017), attend higher education (Sebba et al, 2015), or to be in employment (Viner and Taylor, 2005;Wade and Dixon, 2006) than their non-looked after peers.…”
Section: Introductionmentioning
confidence: 99%